Fuzziness in Information Systems How to Deal with Crisp and Fuzzy Data in Selection, Classification, and Summarization /: How to Deal with Crisp and Fuzzy Data in Selection, Classification, and Summarization. (2016) - Hudec, Miroslav
No abstract available